The theme of paralysis in "Dubliners 100" - Poważa-Kurko, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper analyses the sources of paralysis in "Dubliners 100", which is a collection of "cover versions", as its editor, Thomas Morris, called them, of James Joyce`s collection. They were written by different authors and published in 2014 to commemorate the centenary of the publication of Joyce`s "Dubliners". The only common denominator they share with one another and their great predecessors is the theme of paralysis. Whereas in Joyce`s "Dubliners" religious motifs are ubiquitous, they are almost absent from "Dubliners 100".
Keywords: "Dubliners"; "Dubliners 100"; Joyce, James (1882-1941); paralysis; modernism